Engineering dual-driven pro-angiogenic nanozyme based on porous silicon for synergistic acceleration of burn infected wound healing - Wei Duan; Yue Gao; Ruru Xu; Sheng Huang; Xueqian Xia; Jingwen Zhao; Longhuan Zeng; Qiaolin Wei; Jia-Wei Shen; Jianmin Wu; Yongke Zheng (Materials Today Bio)
The high mortality risk of burn infected wounds has dictated the clinical need for the development of new biomaterials that can regulate multiple aspects of the healing process in a high-quality manner. Although nanozymes have made progress in inflammation modulation and antibacterial management, they often lack the ability in pro-angiogenesis, which greatly limits their functional application in the synergistic treatment of burn infected wounds. In this study, a smart pro-angiogenic nanozyme is simply and efficiently synthesized by in situ reduction of Pt precursors on porous silicon (PSi) nanocarriers. Owing to the hybridization of Pt, the Pt-decorated PSi (Pt@PSi) nanocomposites exhibit excellent near-infrared (NIR) photothermal activity and peroxidase-like catalytic activity, which can be used for co-efficient antibacterial treatment. After exposure to 808 nm NIR laser, Pt@PSi-based photothermal and nano-catalytic combined therapy can achieve more than 95 % bacterial inhibition in vitro. More importantly, under the stimulation of NIR laser and nanozyme, the smart Pt@PSi nanocomposites can efficiently release bioactive inorganic Si ions from the PSi skeleton, which can efficiently promote endothelial cell migration, tube formation, and angiogenesis. Furthermore, In vivo animal studies have demonstrated that Pt@PSi-based combination therapy can significantly accelerate the healing of infected burn infections by inhibiting bacterial growth, scavenging reactive oxygen species, and promoting angiogenesis with a favorable biosafety. Overall, the dual-driven pro-angiogenic nanozyme based on PSi expands the functional application of nanozyme, providing a novel combined strategy for efficient care of difficult-to-heal burn infected wounds.